Revenue management using seat utilization programme : a Japanese restaurant case study. - Ng, Eileen Yu Ting. (2012)
Seat optimization is a tool widely used in restaurant revenue management. This study analyses data from a Japanese restaurant, using an optimization technology known as AIMMS to identify the potential for better seat utilization and higher revenue to be obtained. Leveraged on Linear Programming, a model was built to investigate if minimizing the number of empty seats at occupied tables engenders better seat utilization than the present First-Come-First-Serve practice. The results obtained coincide with our original prediction: by minimizing the number of empty seats at occupied tables, seat utilization improves from 1.05% to 15.13%, with an average increase of 5.78%. The augmentation of potential revenue to be generated as a result of more empty seats averages 2.32% of the current revenue generated by the FCFS practice, with the highest percentage change in potential revenue being 7.8% and the lowest at 0.40%. The study also conducts a sensitivity analysis to reflect a more realistic input of the restaurant’s demand. Similar results are obtained: higher seat utilization and higher potential revenue are recognized when the demand increases.